Systematic energy band gap control of pyrene based donor-acceptor-donor molecules for efficient chemosensor. (July 2021) - Kim, So-Yeon; Kim, Min-Ji; Ahn, Mina; Lee, Kyeong-Min; Wee, Kyung-Ryang
Abstract: We have successfully prepared a series of pyrene based donor-acceptor-donor (D-A-D) molecules, 1, 6-bis[( N, N - p -(R)-diphenylamino)phenyl]pyrene (R = CN (Py-CN ), F (Py-F ), H (Py-H ), Me (Py-Me ), and OMe (Py-OMe )), containing N, N -bis( p -(R)-phenyl)aniline as an electron donor and pyrene as an electron acceptor by using the Suzuki-Miyaura cross-coupling reaction in good yield and fully characterized. By introducing various N, N -bis( p -(R)-phenyl)aniline derivatives with electron-donating or electron-withdrawing R groups, the energy band gaps of Py-R were systematically controlled and emission colors were efficiently tuned from blue to yellow (441–536 nm). Absorption spectra of all Py-R compounds showed intramolecular charge transfer (ICT) transitions in the range of 350–450 nm in the ground state. Solvent-dependent emission spectra confirmed the substituent dependence of charge transfer ability in the excited state. Then, the charge transfer tendencies by the substituents were quantitatively observed using the Lippert-Mataga equation. The HOMO and LUMO energy levels of synthesized Py-R compounds were found in the range of −5.44 to −5.97 eV and −2.68 to −2.97 eV respectively from cyclic voltammetry (CV) experimental. Theoretical studies were conducted using density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations to provide a basis for interpreting experimental data. Experimental and calculated values were found to be well correlated with the Hammett constants (σ para ) and confirmed that the energy band gap was systematically controlled by the substituent effect. Furthermore, pyrene based D-A-D compounds with controllable band gap were employed as selective chemosensors to detect nitro explosives, and especially Py-CN demonstrated efficient sensing ability for ortho -nitroaniline ( o -NA) by fluorescence quenching strategy. Graphical abstract: Image 1 Highlights: Design of pyrene based donor-acceptor-donor molecule. Attachment of various substituents to the triphenylamine. Intramolecular charge transfer from triphenylamine (donor) to pyrene (acceptor). Energy band gap adjustment by substituent effect. Application as chemosensor to detect specific material.